2017
DOI: 10.1080/02643294.2017.1376630
|View full text |Cite
|
Sign up to set email alerts
|

Understanding handwriting difficulties: A comparison of children with and without motor impairment

Abstract: The nature of handwriting difficulties have been explored in children with specific developmental disorders. The aim of this study was to investigate the nature of handwriting difficulties in children with dysgraphia, a less studied group who have significant handwriting difficulties in the absence of motor control or cognitive difficulties. The performance of a dysgraphia group aged 8-14 years was compared to a group with Developmental Coordination Disorder and to typically developing (TD) controls. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…However, this did not seem to impact on the handwriting product in this group as there were no significant correlations found between any of the grip strength measures and measures of the handwriting product and process. This is important as previous studies on handwriting performance in children with DCD have reported links between the percentage of pausing and difficulties with legibility (Prunty and Barnett, 2017) and speed (the number of words produced per minute) (Prunty et al, 2013). If pinch strength was impacting on legibility and speed then there would have been a relationship between these variables.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, this did not seem to impact on the handwriting product in this group as there were no significant correlations found between any of the grip strength measures and measures of the handwriting product and process. This is important as previous studies on handwriting performance in children with DCD have reported links between the percentage of pausing and difficulties with legibility (Prunty and Barnett, 2017) and speed (the number of words produced per minute) (Prunty et al, 2013). If pinch strength was impacting on legibility and speed then there would have been a relationship between these variables.…”
Section: Discussionmentioning
confidence: 95%
“…Future research could examine more closely the differences in pen pressure associated with different letters. Indeed, this would be worth examining in more detail in the future as a lack of force control may be a factor in within-word pausing in children with DCD where they have a tendency to pause in between letters (Prunty et al, 2014;Prunty and Barnett, 2017). While this within-word pausing is likely to be attributed to incorrect letter formation (Prunty and Barnett, 2017), it may also be driven by difficulties coordinating the movements to manipulate the pen.…”
Section: Future Researchmentioning
confidence: 99%
“…Lastly, it should be considered that changes in handwriting impair the children's performance in the classroom, and the teachers must be prepared to help them every way they can, with strategies to compensate such difficulty 25 . To this end, it is necessary to invest in scientific production on the theme of dysgraphia and include it in teachers' training, as the literature makes evident the limited knowledge about the neuropsychomotor development and the perception of changes in fine motor control and, more specifically, in handwriting, which would be related to signs of dysgraphia 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…The design of the Write-Rite application addresses problems inherent in dysgraphic children based on the following principles (Prunty & Barnett, 2017) in that the application: 1. Allows the teacher to monitor progress in students' handwriting performance.…”
Section: Design Principlesmentioning
confidence: 99%